KINETIC PARAMETERS OF PHENOL BIODEGRADATION WITH DIFFERENT MICROORGANISMS: A REVIEW - MIZZOURI, NASHWAN SHAWKAT (Journal of Duhok University, 2017)
Most industries release wastewater contains high concentrations of phenol which is toxic and contaminating the environment. Biological treatments are preferable for the phenolic compounds treatment. This review aims to investigate the impacts of temperatures, pH, and concentration of substrate on the phenolic compounds biodegradation, to compare the kinetic parameters of different microorganisms, and to discuss the different between the kinetic parameters of aerobic and anaerobic treatment. The review showed that most of the phenol biodegrading bacteria are P. Putida species and mixed cultures but P. Putida has a better adaptation to phenol biodegradation. The values of µmax and Ks in anaerobic process are smaller than the values attained in aerobic process. The optimum temperature to acclimatize bacteria to the phenol substrate is 30 ºC while the optimum pH condition is between 6.5 and 7.5. As the phenol concentration was increased, there was an increase in the values of the Ks and even when concentration is low; phenols have a significant inhibitory impact on (μ). The values of Ki for phenol degradation for P. putida species were higher than the values of Ki of mixed cultures. The highest Ki value for the phenol degrading among P.Putida species was 1185.8 mg/L and the highest Ki value among mixed cultures was 648.1 mg/L and the highest Ki value among the other species was 2434.7 mg/L.